The Role of Islamic Pedagogy in Developing Moral and Ethical Leaders for the 21st Century - Huzaiman Hushin; Mahmoud Abdullah; Mukhlis Mukhlis; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
This study investigates the role of Islamic pedagogy in developing moral and ethical leaders for the 21st century. By focusing on the teachings of Islamic scholars, the paper examines how Islamic educational systems emphasize the development of character, leadership skills, and ethical decision-making in students. The research highlights how Islamic pedagogy, with its focus on integrity, justice, and responsibility, contributes to shaping future leaders who are not only intellectually competent but also morally grounded. The study also evaluates contemporary Islamic educational institutions and their efforts to instill leadership qualities in students. The paper concludes by offering practical recommendations for integrating Islamic pedagogical principles into leadership development programs in educational settings